Supply Chain Strategy in Tourism Industry for Antecedents and Consequences of Foreign Tourists Shopping Satisfaction on Revisit Intention at Traditional Souvenir Market - Wayan Ardani; Ketut Rahyuda; I Gusti Ayu Ketut Giantari; I Putu Gde Sukaatmadja (International Journal of Supply Chain Management, 2020)
Abstract. The paper aims to investigate the possible relationship between tourism supply chain and strategic partnership, read as a way to reduce and better manage the complexity in tourism industry. The previous studies on satisfaction in tourism have attracted the attention of practitioners and academicians, but its consequences on tourists revisit intention at traditional retail has not been widely carried out. This study aims to explain the factors that influence satisfaction as well as its consequences on revisit intention of tourists at the traditional souvenir market in Bali through the supply chain management (SCM) system. In addition, it also explained the role of sources of WOM (offline and online) as a moderator of the relationship between service quality and product quality towards tourist satisfaction. A survey was conducted from foreign tourists who visited and experienced to shop souvenirs at the traditional market in Bali. The data were analyzed using the SEM-PLS approach. This study revealed that SCM had a positive and significant effect on trust, satisfaction, and revisit intention. Product and service quality had a positive and significant effect on trust, satisfaction, and revisit intention. Trust had a positive and significant effect on satisfaction and revisit intention. Satisfaction had positive and significant effect on revisit intention. However, the source of WOM (offline and online) did not significantly moderate the effect of service quality and product quality towards satisfaction. This study proved product quality was the most influential factor impacting satisfaction. The ability to maintain consistency of service quality and product quality were very important factors in creating tourists trust, satisfaction and revisit intention. Finally, this model is expected to contribute in determining the SCM that influence tourist satisfaction at souvenir traditional market.